U.S. Navy fundamentals of war gaming - McHugh, Francis J. (SkyhorsePublishing, 2013)
Offers a historical perspective on military gaming and the evolution of the tools and tactics used in ancient times up through modern computer simulations and includes examples of one- and multi-sided games as well as free-play and rigid-style games.